Efecto de un alimento elaborado a base de torta de soya predigerida sobre el crecimiento y la supervivencia del paco Piaractus brachypomus en la fase de alevinaje - Sandoval Flores, Lilian (2024)
This present study was carried out at the facilities of the Alto Amazonas Agrarian Agency between November 2022 - April 2023, with the purpose of evaluating the growth of “paco”, Piaractus brachypomus, fed with a diet based on predigested soybean cake (TSP) and grown under a closed recirculation system. The recirculation system was made up of 9 experimental units such as 160 l plastic trays, applying 3 treatments (T1=30% TSP; T2=40% TSP and T3=50% TSP), each treatment with 3 repetitions, with 9 experimental units; Likewise, the diet digestibility study was carried out. The results show greater use in the fish fed with the T3 treatment, achieving greater growth in weight and length, finding a significant difference (p<0.05) between the treatments evaluated; Likewise, a significant difference (p<0.05) was found in the specific growth rate (SGR), feed conversion factor (FCA) and survival (S), unlike the condition factor parameter (K), who recorded similar values; On the other hand, water quality parameters were recorded within the acceptable range for the species. It is concluded that in relation to the productive parameters of the paco P. brachypomus, with T3 it registers a greater gain in weight and length.